Dampak Globalisasi Ekonomi Terhadap Stabilitas Lembaga Keuangan Perbankan: Studi Kasus Pada Negara Berkembang - Windi Octaviani; Theresia Sihombing; Joan Agus Sirait; Radja Marihat Batu Bara; Hasyim Hasyim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Economic globalization has become one of the main distinctive features in the development of the world economy today. This phenomenon has a significant impact on various aspects of economic life, including the stability of banking financial institutions in developing countries. This study aims to investigate the impact of economic globalization on the stability of banking financial institutions using a case study approach in specific developing countries. Through in-depth analysis, this study will examine the factors affecting the stability of banking financial institutions in the face of economic globalization, as well as their implications for economic and financial policies. The results of this study are expected to provide valuable insights into the impact of economic globalization on the stability of banking financial institutions in developing countries. The practical implications of the research findings will be discussed in the context of economic and financial policy, with the aim of strengthening the financial system and increasing resilience to global market fluctuations